Systemic Acrolein Elevations in Mice With Experimental Autoimmune Encephalomyelitis and Patients With Multiple Sclerosis - Tully, Melissa; Tang, Jonathan; Zheng, Lingxing; Acosta, Glen; Tian, Ran; Hayward, Lee; Race, Nicholas; Mattson, David; Shi, Riyi (Frontiers in Neurology, 2018)
Demyelination and axonal injury are the key pathological processes in multiple sclerosis (MS), driven by inflammation and oxidative stress. Acrolein, a byproduct and instigator of oxidative stress, has been demonstrated as a neurotoxin in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. However, due to the invasive nature of acrolein detection using immunoblotting techniques, the investigation of acrolein in MS has been limited to animal models. Recently, detection of a specific acrolein-glutathione metabolite, 3-HPMA, has been demonstrated in urine, enabling the noninvasive quantification of acrolein for the first time in humans with neurological disorders. In this study, we have demonstrated similar elevated levels of acrolein in both urine (3-HPMA) and in spinal cord tissue (acrolein-lysine adduct) in mice with EAE, which can be reduced through systemic application of acrolein scavenger hydralazine. Furthermore, using this approach we have demonstrated an increase of 3-HPMA in both the urine and serum of MS patients relative to controls. It is expected that this noninvasive acrolein detection could facilitate the investigation of the role of acrolein in the pathology of MS in human. It may also be used to monitor putative therapies aimed at suppressing acrolein levels, reducing severity of symptoms, and slowing progression as previously demonstrated in animal studies.